Tafsir Mimpi dalam Pandangan Hadis: Studi Takhrij dan Syarah Hadis - Hikmawan Akbar (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the interpretation of dreams. This research uses a qualitative approach by applying the analytical descriptive method. The formal object of this research is the science of hadith, while the material object is the hadith about the interpretation of dreams in Ahmad's narration No. 7321. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Ahmad No. 7321 is relevant to be used as an enrichment of knowledge in the field of dream interpretation.